TIPOLOGI KEPRIBADIAN TOKOH PADA FILM GEZZ AND ANN KARYA NADHIFA ALLYA TSANA - Linda Eka Pradita; Siti Roqidah; Ulfah Kusumawati; Tiara Anggerdyah; Mukhibatur Rohmah; Bekti Wulandari (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
Film is a popular visual media that can be watched by various ages according to category. The film presents an interesting story with many building elements. Building elements include many things, one of which is the character's personality typology. Personality typology classifies humans in several ways, namely extroverted and introverted personalities. The research entitled